Academic Behavior from the Perspective of the Fraud Hexagon Theory (An Empirical Study of Master’s Degree Accounting Students in South Kalimantan Province) - Putri, Audri Helmina; Adriani, Ade; Yuliani, Rahma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines academic behavior from the perspective of the Fraud Hexagon Theory, which includes pressure, opportunity, rationalization, capability, arrogance, and collusion. The purpose of this research is to analyze the influence of these six factors on academic fraud behavior among Master’s degree students in Accounting in South Kalimantan Province. This study employs a quantitative approach using primary data collected through questionnaires distributed to Accounting postgraduate students. The data were analyzed using statistical techniques to test the proposed hypotheses. The results indicate that pressure, opportunity, rationalization, capability, arrogance, and collusion have varying effects on academic fraud behavior, either individually or simultaneously. These findings provide empirical evidence that the Fraud Hexagon Theory can be applied to explain academic misconduct in higher education. This study is expected to contribute to the development of academic integrity policies and preventive strategies to reduce academic fraud in postgraduate education.